Pengaruh Pola Asuh Otoriter, Demokratis, dan Permisif Terhadap Kualitas Interaksi Karyawan: The Influence of Authoritarian, Democratic, and Permissive Parenting on the Quality of Employee Interaction - Elma Magdalena Tamba; Daniela Putri Ramadhanty; Nashwa Khoirunnisa; Septi Gusti Fitriani; Widya Nurliana; Rudianto Rudianto (CV Warnak Johanna Nusantara, 2026)
Abstracts - Social skills of employees, such as their ability to work together, communicate, and form relationships with others, especially in the workplace, are greatly influenced by the parenting style applied by their parents. A quantitative approach with several research variables was used as the methodology by distributing questionnaires to research subjects aged 19-24 years, resulting in a sample size of 154. Data analysis in this study was carried out through several steps, such as validity and reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, hypothesis testing using t-tests and F-tests, and determination coefficient assessments. The findings of this study indicate that parenting practices do have a significant influence on how children interact with their social environment, especially in their work environment.Keywords: parenting patterns, behavior, work environment